PENGARUH FREQUENT CEO’S PICTURE DAN FAKTOR LAINNYA TERHADAP FRAUDULENT FINANCIAL STATEMENT - SHELLA PUTRI RIANA; INDRA ARIFIN DJASHAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to obtain empirical evidence regarding the effect of financial stability, external pressure, financial targets, effective monitoring, institutional ownership, nature of industry, change in auditor, company size, change of director, frequent CEO's picture on fraudulent financial statements. This study uses companies listed on the Indonesia Stock Exchange in the manufacturing sector for the period 2021 to 2023. The sample in this study was 66 companies that had passed the five sample criteria. The data were analyzed through descriptive statistical tests, data quality tests, classical assumption tests dan hypothesis testing using multiple linear regression methods with the IBM SPSS Statistic 25 program. The results of this study indicate that financial stability, external pressure, nature of industry, effective monitoring, and change in auditor have an influence on fraudulent financial statements. While financial target, institutional ownership, company size, change of director, and frequent CEO's picture do not have an influence on fraudulent financial statements.